The Effect of Perceived Organizational Support and Nonphysical Work Environment on Retention - Dewi; Astaginy, Niar; Ismanto, Ismanto (Perkembangan Kajian Sosial, 2025)
This study aims to determine: how the influence of Perceived Organizational Support and Non-Physical Work Environment on Employee Retention at PT. DJL Afd. IX. This study is a study with a quantitative approach. Data collection through Observation, Literature Study, and Questionnaire Distribution. The population in this study were all workers at PT. DJL Afd. IX. Determination of sample size using the Hair formula (2014) which is 50 people by multiplying the number of indicators by a minimum value of 5-10. Testing of research instruments using validity tests and reliability tests with SPSS The data analysis technique used in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using the Smart-PLS 3.0 application. Based on the calculation results, it can be seen that the Original Sample Estimate value of Non-Physical Work Environment on Retention is 0.587 and the T-Statistic is 5.409 with a P-Value of 0.000. Likewise, Perceived Organizational Support (POS) on Retention is worth 0.321 and T-Statistic is 2.586 with a P-Value of 0.010.